Sedimentological studies in the late Precambrian and lower Cambrian rocks of east Finnmark - Banks, N (1971)
In eastern Finnmark a northward thickening wedge of late Precambrian and Cambro-Ordovician sedimentary rocks extends 200km from east to west, with a maximum north- south width of approximately 50km. The succession lies unconformably upon Precambrian crystalline basement, which crops out to the south. The maximum thickness is between 4,000m and 5,000m with shallow water sandstones and shales predominating. Two distinct tillite formations occur, beneath each of which there is an unconformity shown only by local downcutting and slight regional discordance. Otherwise the succession is conformable, deposition having occurred in a gently subsiding basin. Structural deformation is very slight in the east but increases towards Laksefjord in the west where the rocks are strongly folded. In the far west of the area two distinct units are present, the Gaissa Nappe consisting of folded Precambrian sandstones and, underlying this, the autochthonous undeformed Dividal Group (previously the "Hyolithus Zone") of late Precambrian and Lower Cambrian age. This study is concerned with the six members which form almost the entire succession from the top of the Upper Tillite to the top of the Lower Cambrian. These members are the Innerelv and Manndraperelv Members of the Stappogiedde Formation, the Lower and Upper Members of the Breivik Formation and the Lower and Upper Members of the Duolbasgaissa Formation The lower three members are found over a wide area and can be correlated with the Members of the Dividal Group in the extreme southwest of the region. Their maximum thickness of about 775m is found on the Digermul Peninsula and gradual thinning occurs towards the southwest, the thickness of the Dividal Group being about 230m. It is possible that some slight thinning also occurs on the Varanger Peninsula to the southeast of the Digermul Peninsula. The upper three members are confined to the Digermul Peninsula and have a maximum thickness of about 900m. The majority of the sediments are thought to have been deposited in a variety of offshore shallow marine environments. Within such environments it is considered that there are five main processes by which sand can be transported. These are i) semipermanent currents, ii) tidal currents, iii) wave drift currents, iv) coastal storm surge currents, v) river-generated currents. From the various known and predicted features of the deposits of each type of current it is possible to deduce which was the most important in transporting and depositing sediment in any given sequences of beds. The base of the Innerelv Member marks a widespread transgression as a result of which quiet water mudstones replaced the coarse fluvial sandstones of the Lillevatn Member. The Innerelv Member consists of mudstones, siltstones and very fine sandstones and has been divided into six intergradational facies, five of which form a series of gradually increasing environmental energy and possibly increasing proximity to a shoreline. In the highest energy facies (I.5) strong currents cut channels but deposited little sand within them, the main sediments being irregularly bedded siltstones and mudstones. In the lower energy facies the beds have a more sheet like form. Palaeocurrent directions where measurable, are unimodal except in the highest energy facies where they are variable. Coastal storm surge currents are believed to have deposited the majority of the sandstone and siltstone beds in this member but the evidence is insufficient to rule out a river generated or tidal origin. The Manndraperelv Member consists of three bands of red and white sandstone separated by two bands of green mudstone and siltstone with interbedded graded sandstones. The lowest sandstone band follows gradationally from the Innerelv Member in the east but in the southwest, where it is thinner, it sits sharply and probably disconformably upon the underlying member. Sedimentary structures are poorly seen in it and no conclusions were reached as to the mode of sediment transport except that wave activity was probably important in producing the many irregular bedding surfaces which are present. The two bands of green mudstones and siltstones with graded sandstones pass up into red and white sandstones similar to those of the lower red sandstone bend in two coarsening upward sequences. As suggested by Reading (1965) the graded sandstones are probably turbidites. The overlying red and white sandstones are thought to be mainly shallow marine "shelf" deposits and thus the transitions represent shallowing (regressive) sequences. In the first coarsening upward sequence in the most northeasterly exposure sandstones with low angle cross-bedding are interpreted as beach deposits and the siltstones which overlie them are probably lagoonal. These are in turn overlain by a sequence of sandstones in which bed thickness decreases upwards. These sandstones are interpreted as transgressive offshore deposits. The presence of these beds in the most northeasterly exposure fits with the palaeocurrent evidence in the turbidites to suggest that the shelf and shoreline prograded to the southwest or west although in detail the history is more complex. The two coarsening upward sequences thin to the south- west of the Digermul Peninsula and in theDividal Group are not developed, these sediments probably having been deposited under continuously deep water conditions. The Lower Breivik Member consists of a complex alternation of siltstones, mudstones and various types of sandstones. On the Digermul Peninsula and in the Leirpollen area the sandstones occur as beds up to l00cm thick and vary in grain size from very fine to coarse sand. Very fine and fine sandstones predominantly show parallel lamination and cross-lamination and have varying amounts of matrix. Medium to coarse sandstones have little or no matrix and are mostly cross-bedded. The majority of the beds have erosive bases and appear to have been deposited by waning currents. The palaeocurrent distribution in the sandstones is bipolar which suggests a tidal origin for these beds. Fluctuations in current strength produced beds of varying grain size and thickness and were the result of natural variation within the tidal cycle, the affect of storms, and the closeness of the basin to resonance. The Lower Breivik Member in the Laksefjord area and the laterally equivalent Member IV of the Dividal Group show some differences from the eastern sections, red sandstones being a distinctive feature of the parts of the Member around Laksefjord. The Upper Breivik, Lower Duolbasgaissa and Upper Duolbasgaissa Members form an irregular coarsening upward sequence. The Upper Breivik Member consists mainly of green siltstone with beds of very fine sandstone mostly less than 20cm thick. The sandstone beds commonly have erosive bases and are sometimes graded. The Lower Duolbasgaissa Member consists mainly of thin to medium-bedded fine sandstones with interbedded siltstones and mudstones. However, it also contains a 20m thick unit of cross-bedded fine sandstone to granule conglomerate. In the Upper Duolbasgaissa Member 5-50m units of crossbedded sandstone predominate and thinner bedded sandstones are less common. Sets of cross-bedding up to 4m high occur. Bipolar palaeocurrent directions are found throughout these three members and all gradations can be seen between the various sandstone types. It is suggested that tidal currents were again the most important mechanism of sediment transport. Two distinct axes of transport are present; NW-SE and SW-NE. The change from one tidal pattern to the other was probably caused by changes in basin physiography. By comparison with recent sediments in the seas around Great Britain the different types of sandstones are believed to have been deposited at various positions along tidal current transport paths. Down present day paths tidal velocities decrease and there is a concomitant decrease in grain size and change in the sedimentary structures. The thickest cross-beds are interpreted as sand wave deposits and smaller ones formed from megaripples. Palaeocurrent data and lateral facies variation suggests the possibility of a shoreline to the northeast at least in Manndraperelv Member times and in the upper part of the succession. The sandstone petrography suggests that the source area consisted of acid igneous rocks with subsidiary metamorphic and sedimentary rocks. Consideration of the regional geology suggests that although the nearest shore- line may have been to the northeast the source area must have been the Precambrian shield area to the southeast. Where tidal sediments are present a connection to an ocean is inferred. In the entire late Precambrian and Cambro-Ordovician succession trace fossils first appear in the Innerelv Member. Their abundance and diversity increases rapidly in the latest Precambrian and early Cambrian sediments. The absence of biogenic activity in older sediments is not due to the lack of suitable sedimentary facies. The incoming and diversification of trace fossils reflects principally the development of the Phyla Annelida, Arthropoda and Moilusca. The build up of atmospheric oxygen is considered the most likely fundamental factor controlling the development of life.